Autorschaft im Film – Das Beispiel Werner Herzog - Erstić, Marijana (Anafora, 2024)
This article deals with Werner Herzogʼs authorship, since his films of the 1970s and 1980s belong to German movies made by auteur directors or to the New German Cinema. The focus is on his feature films and his autobiography. After the introductory considerations on literary and cinematic authorship, Werner Herzog is first introduced as a literary author. This is followed by the history of French and German movies made by auteur directors before a concluding section discusses Herzogʼs cinematic authorship based on his best-known film Fitzcarraldo. The aim of the article is to analyse and contextualise the elements of this authorship, such as work, autobiography, and autoreflection.